2019
DOI: 10.1371/journal.pone.0212929
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-mediated breeding performance of Lewis’s Woodpeckers (Melanerpes lewis) in British Columbia

Abstract: Tree cavities provide a critical resource for cavity-nesting animals, and high quality cavities can be difficult for animals to acquire in habitats where competition is high. We investigated the breeding performance of Lewis’s Woodpeckers in three habitat types in British Columbia, Canada in 2013 and 2014. We also assessed whether the number of nest competitors and cavity availability influenced the habitat specific breeding performance of this threatened cavity nesting species. We found that daily nest surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 39 publications
(54 reference statements)
3
11
0
Order By: Relevance
“…Recent work in British Columbia revealed nest success of Lewis’s Woodpeckers in cottonwood floodplain forests more comparable to those in our study (79%;), but with low nest success in the burned forest (15%; high intensity and 10–15 years post‐fire; Macfarland et al. 2019). Such low nesting success contrasts with those of studies of nest success of other woodpecker species, with nest success often reported to be above 90% and rarely below 70% (Li and Martin 1991, Martin 1995, Stillman et al.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Recent work in British Columbia revealed nest success of Lewis’s Woodpeckers in cottonwood floodplain forests more comparable to those in our study (79%;), but with low nest success in the burned forest (15%; high intensity and 10–15 years post‐fire; Macfarland et al. 2019). Such low nesting success contrasts with those of studies of nest success of other woodpecker species, with nest success often reported to be above 90% and rarely below 70% (Li and Martin 1991, Martin 1995, Stillman et al.…”
Section: Discussionsupporting
confidence: 81%
“…However, similar nest success in our floodplain forest and in British Columbia (Macfarland et al. 2019), along with the lower nest success reported by Saab and Vieling (2001), suggests the possible importance of landscape context or internal degradation (e.g., grazing) impacts when evaluating the potential value of floodplain forests for Lewis’s Woodpeckers (Tewksbury et al. 2006).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations